2020
DOI: 10.1002/rcr2.519
|View full text |Cite
|
Sign up to set email alerts
|

Transnasal humidified rapid insufflation ventilatory exchange during bronchoscopy in severe pulmonary hypertension due to Gerbode defect

Abstract: Transnasal humidified rapid insufflation ventilatory exchange (THRIVE) has been shown to prevent desaturation and prolong apnoeic time in the perioperative setting. Previously, pulmonary hypertension was not studied using this technique, due to concern for hypercapnia and resultant transient worsening of mean pulmonary artery pressure. We describe a patient with severe pulmonary hypertension (mean pulmonary artery pressure of 82 mmHg) who underwent bronchoscopy using deep sedation with THRIVE. There were no re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…THRIVE uses a relatively constant concentration, temperature, and humidity at a high flow rate of up to 70 L/min via the nasal cannula. Studies have shown that THRIVE can extend the asphyxia window for patients under general anesthesia to 65 min for patients with difficult airway management [ 13 ]. Hua and colleagues found that THRIVE significantly extended the SAT in elderly patients after rapid sequence induction of anesthesia compared to facemask [ 5 ], which is consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…THRIVE uses a relatively constant concentration, temperature, and humidity at a high flow rate of up to 70 L/min via the nasal cannula. Studies have shown that THRIVE can extend the asphyxia window for patients under general anesthesia to 65 min for patients with difficult airway management [ 13 ]. Hua and colleagues found that THRIVE significantly extended the SAT in elderly patients after rapid sequence induction of anesthesia compared to facemask [ 5 ], which is consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Possible reasons are as follows: (1) THRIVE uses a nasal catheter to administer high-concentration and high-flow oxygen and is unaffected by tooth loss. (2) THRIVE facilitates oxygenation by delivering high-flow pure oxygen with a maximum velocity of 70 L/min and a small amount of CPAP, which opens the upper respiratory tract and even the distal airway, decreasing ventilatory dead space and reducing the likelihood of atelectasis [ 13 ]. (3) The facemask usually needs to be removed during endotracheal intubation, which leads to an interruption of oxygenation.…”
Section: Discussionmentioning
confidence: 99%
“…THRIVE uses a relatively constant concentration, temperature, and humidity at a high ow rate of up to 70 L/min via the nasal cannula. Studies have shown that THRIVE can extend the asphyxia window for patients under general anesthesia to 65 minutes for di cult airway management [13]. Hua and colleagues found that THRIVE signi cantly extended the safe apneic duration in elderly patients after rapid sequence induction of anesthesia compared to facemask [5].…”
Section: Discussionmentioning
confidence: 99%
“…THRIVE also provides a small amount of continuous positive airway pressure (CPAP), potentially opening the upper respiratory airway and even the distal alveoli and so reducing ventilatory dead space. This may help reduce the occurrence of atelectasis and increase alveolar ventilation [13]. This mechanism may contribute to the prolongation of the safe apneic duratioshorten the reoxygenation time.…”
Section: Discussionmentioning
confidence: 99%